PERPANJANGAN WAKTU DAN TAMBAHAN BIAYA GADAI EMAS PERSPEKTIF HUKUM ISLAM: (Studi Kasus di Peagadaian Syariah Unit Bone) - Nuraini Firsan; Asni Zubair; Firdaus Firdaus; Muammar Hasri; A. Sultan Sulfian (Jurnal Al-Kharaj: Studi Ekonomi Syariah, Muamalah, dan Hukum Ekonomi, 2026)
Abstract This study discusses the mechanism of extension of time and additional fees of pawning gold form an Islamic law perspective (case study at the bone unit of the Islamic pawnshop). The main focus is how the process is implemented and its compliance with sharia principles. The research method used is empirical juridical to analyse field practices and normative theological to assess sharia compliance. The results of the study indicate a lack of transparency and detailed information regarding the time extension mechanism and cost details for customers, even though the costs are claimed as mu'nah (maintenance/administrative) costs. This lack of detail and transparency creates gharar (uncertainty), which is prohibited under Islamic law due to its potential for harm and triggering disputes. This study recommends that Islamic pawnshop evaluate and revise their operational procedures, increasing transparency and clarity of information, to ensure full alignment with sharia principles that uphold fairness, openness, and the avoidance of gharar. Keywords: Gold pawn, time extension, Islamic law